Study on Dynamic Erosion Behavior of 20# Steel of Natural Gas Gathering Pipeline - Dongli Lv; Zhanghua Lian; Lindong Liang; Qichao Zhang; Tao Zhang (Advances in Materials Science and Engineering)
In this paper, a finite element model for the particle-impact target is established for the abrasion erosion failure behavior of 20# steel used in natural gas gathering pipelines. The JC plastic model and failure criterion are used in the model to simulate the failure and damage of the material, and the reliability of the model was verified by comparison with experimental data. The dynamic behavior of particle erosion was studied by using this model. The changes of energy, stress, and morphology at the microscopic level were analyzed. The influence of particle shape, particle size, impact velocity, and impact angle on the erosion rate of 20# steel was obtained. The model is further used to study the influence mechanism of stress interference on erosion damage behavior under multiparticle random drop impact.